2016
DOI: 10.3138/cjhs.251-a4
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of socio-demographic and behavioural factors among immigrant MSM in Montreal from an HIV-testing site sample

Abstract: Little Canadian research exists on immigrant men who have sex with men (MSM), who are internationally reported to use rapid HIV-testing sites. Our objective was to describe immigrant MSM in a sample of clients at an HIV testing site. From July 2012 to November 2013, clients at Actuel sur Rue (AsR), a Montreal-based HIV rapid-testing site, provided data for a staff- and a self-administered questionnaire. We compared immigrant and non-immigrant MSM's socio-demographics and risk practices. Among immigrants, we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…LGBTQþ communities in Canada experience income and other socioeconomic disparities relative to their white counterparts (George et al, 2007;Lachowsky et al, 2017;Lessard et al, 2016;Millett et al, 2012;Nakhaie & Wijesingha, 2015).…”
Section: Racializedmentioning
confidence: 99%
See 1 more Smart Citation
“…LGBTQþ communities in Canada experience income and other socioeconomic disparities relative to their white counterparts (George et al, 2007;Lachowsky et al, 2017;Lessard et al, 2016;Millett et al, 2012;Nakhaie & Wijesingha, 2015).…”
Section: Racializedmentioning
confidence: 99%
“…In our review of the literature reporting socioeconomic data on LGBTQ+ newcomers and racialized communities, we found a number of unique manifestations of poverty reflected in the social conditions and experiences of those in these groups. First, particularly in studies of sexual health among men who have sex with men (MSM), we found that racialized MSM frequently report disparities in income and employment relative to their white counterparts ( George et al, 2007 ; Lessard et al, 2016 ; Millett et al, 2012 ). For example, in one meta-analysis of the health behaviors and health outcomes of MSM across the United States, Canada, and the United Kingdom, Canadian Black MSM appeared to be approximately 1.56 times more likely than their non-Black counterparts to report incomes under US$20,000 ( Millett et al, 2012 ).…”
Section: Lgbtq2s+ Poverty In Canada: An Intersectional Narrative Reviewmentioning
confidence: 99%
“…They found that age (younger), education (less educated), income (low income), heavy drinking, smoking, and use of nitrite inhalants (i.e., poppers) increased risky behaviour in HIV seronegative gay men [ 35 ]. Adding to the sociodemographic profile of risk, Lessard, Lebouché, Engler, and Thomas [ 36 ] compared immigrant and non-immigrant men visiting an HIV testing site. They found that immigrant clients had a lower income and more education and were younger and more often unemployed.…”
Section: Resultsmentioning
confidence: 99%
“…They found that immigrant clients had a lower income and more education and were younger and more often unemployed. Fewer immigrant men reported ‘risky’ sexual behaviours such as unprotected sex with a HIV-positive partner or receiving goods or services in exchange for sex [ 36 ]. Ross and colleagues [ 37 ] have contributed to the literature on bisexuality with a specific focus on mental health and substance use and the relationship between bisexuality, low socio-economic status, and mental health [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The MSM community accounts for the largest proportion among the newly infected HIV population in the United States (Wray, Kahler, & Monti, 2016). It has been reported that the high rate of HIV infection is associated with high rates of unprotected sexual behaviors such as unprotected anal intercourse within MSM population in other countries (Do Amaral, Abdo, Tavares, & Scanavino, 2015; Lessard, Lebouché, Engler, & Thomas, 2016).…”
Section: Introductionmentioning
confidence: 99%